Distribution of Ticks from the Genus Dermacentor (Acari, Ixodidae) in Ukraine - Akimov, I.A.; Nebogatkin, I.V. (Вестник зоологии, 2011)
The northern border of present range of the tick species Dermacentor marginatus is determined on the territory of Ukraine in Volyn, Rivne, Khmelnytsky, Zhytomyr, Kyiv, Cherkasy, Poltava and Sumy oblasts. D. reticulatus species was revealed to be adapted for living in urbanized areas as parasitizing domestic and stray animals, small mammals. It also inhabits shores of artificial reservoirs and occurs in the steppe zone, except for arid areas. D. reticulatus preimaginal stages are found for the first time on birds (Anas platyrhynchos, Sturnus vulgaris, Turdus merula, T. viscivorus).